PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT TAMBANG MITRA JAYA DI JAKARTA SELATAN - Dede Diaz Azaqi; Prasetyo Kurniawan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of job satisfaction and organiza-tional commitment partially and simultaneously on employee performance at PT Tambang Mitra Jaya. The method used is quantitative associative research, mean-ing to determine the relationship between two or more variables. The partial and simultaneous sampling technique uses saturated sampling. The data collection technique in this study uses a questionnaire and obtained a sample of 80 respond-ents. Data analysis uses the SPSS version 25 program. The analysis techniques used are validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficients, determination coefficients and hypothesis testing. The results of this study are job satisfaction has a significant effect on employee performance with a determination coefficient value of 47.6% and the hypothesis test obtained t count> t table or (3.143> 1.665). Job satisfaction commitment has a significant effect on employee performance with a determination coefficient value of 64.3% and the hypothesis test obtained t count> t table or (7.103> 1.665). Work environment and organizational commitment simultaneously have a significant ef-fect on Employee Performance with the regression equation Ŷ = 5.089 + 0.268X1 + 0.598X2 + e, a correlation value of 0.829. The coefficient of determination is 0.679 or 67.9% while the remaining 32.1% is explained by other factors. Hypothe-sis testing obtained a calculated F value > F table or (84.731 > 3.115).